Etnobotani Tumbuhan Obat Tradisional oleh Masyarakat Suku Berau di Kampung Bebanir Bangun dan Gurimbang Kecamatan Sambaliung Kabupaten Berau - Handayani, Fitri; Hendra, Medi; Susanto, Dwi (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
The use of plants has an impact and invaluable knowledge and a wealth of culture that needs to be excavated and preserved so that traditional knowledge about plants remain attached and not lost inedible by age. This research was conducted in the District of Berau tribal communities Sambaliung (Bebanir Bangun and Gurimbang village). Data were collected through semi-structured interviews, field exploration, literature studies, sample preservation, processing and manufacturing of herbarium specimens. Based on the results of research conducted in Bebanir Bangun dan Gurimbang, District Sambaliung, Berau district in obtaining 78 kinds of medicinal plants derived from 38 families and be used as an alternative medicine community. Habitat herbs include yard (56%), riparian (9%), forest (5%) and others (30%) of medicinal plants. Based on the processing method generally tribal communities Berau Bebanir Bangun dan Gurimbang village cultivate medicinal plants to be used in a way crushed and then taped (47%), boiled and drunk (26%), burned or heated (8%), kneaded and massaged (6%), cleaned and then affixed to 5%), grated and filtered (4%), chewed (3%) and flattened (1%).